2015
DOI: 10.1159/000431260
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological Modulation of Mucosa-Related Impairment of β-Adrenoceptor-Mediated Relaxation in Human Detrusor

Abstract: Objectives: The mucosa of human detrusor strips impairs catecholamine-induced relaxation. In order to elucidate which signal transduction pathways are involved in this cross talk between the mucosa and detrusor, we have studied the effects of several pharmacological agonists and antagonists on noradrenaline-mediated relaxation in intact and mucosa-denuded detrusor strips. Patients and Methods: Strips of detrusor tissue were obtained from patients who had undergone cystectomy for bladder cancer and were set up … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 32 publications
0
4
0
Order By: Relevance
“…Relaxing effects of catecholamines are blunted by the presence of the urothelium in the human bladder (Otsuka et al, 2008, Propping et al, 2013, Propping et al, 2015b and are mediated via β2-adrenoceptors (Propping et al, 2013). A similar effect was seen in mouse bladder, and the urothelium reduced the sensitivity of KCl pre-contracted tissues to β-adrenoceptor-induced relaxation to isoprenaline, again via β2-adrenoceptors, although at high concentrations of isoprenaline there was a minor involvement of β3-adrenoceptors (Propping et al, 2015a).…”
Section: Modulation Of Relaxant Responsesmentioning
confidence: 95%
See 2 more Smart Citations
“…Relaxing effects of catecholamines are blunted by the presence of the urothelium in the human bladder (Otsuka et al, 2008, Propping et al, 2013, Propping et al, 2015b and are mediated via β2-adrenoceptors (Propping et al, 2013). A similar effect was seen in mouse bladder, and the urothelium reduced the sensitivity of KCl pre-contracted tissues to β-adrenoceptor-induced relaxation to isoprenaline, again via β2-adrenoceptors, although at high concentrations of isoprenaline there was a minor involvement of β3-adrenoceptors (Propping et al, 2015a).…”
Section: Modulation Of Relaxant Responsesmentioning
confidence: 95%
“…A similar effect was seen in mouse bladder, and the urothelium reduced the sensitivity of KCl pre-contracted tissues to β-adrenoceptor-induced relaxation to isoprenaline, again via β2-adrenoceptors, although at high concentrations of isoprenaline there was a minor involvement of β3-adrenoceptors (Propping et al, 2015a). Whilst in human bladder this inhibitory effect on relaxations was seen in tissues pre-contracted with KCl and carbachol (Propping et al, 2015b), the same authors showed in mouse bladder that the urothelium did not inhibit relaxations if the tissues were pre-contracted with carbachol (Propping et al, 2015a). The rat bladder urothelium does not appear to influence smooth muscle relaxation to β3-adrenoceptor agonists (Kullmann et al, 2011).…”
Section: Modulation Of Relaxant Responsesmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH was 7.4. All drugs were obtained from the same sources and dissolved either in distilled water of dimethyl sulfoxide as in our previous study ( Propping et al, 2015c ). The DMSO concentration in the bath did not exceed 0.3%.…”
Section: Methodsmentioning
confidence: 99%